Job satisfaction amongst special education teachers - Z. S. Alkayed; S. M. Al Ali; M. M. Al Masa’deh (Образование и наука)
Introduction. The level of job satisfaction and attitudes of special education teachers towards working with children with disabilities significantly impact the attitudes of trained student teachers. Positive and satisfied special education teachers serve as role models, inspiring and influencing student teachers in a positive way. On the other hand, if special education teachers are dissatisfied or hold negative attitudes, it can discourage student teachers from pursuing a career in special education. Therefore, promoting job satisfaction and positive attitudes among special education teachers is crucial for fostering a supportive environment that encourages student teachers to embrace the challenges and rewards of working with children with disabilities.                Aim. The present study aimed to measure the level of job satisfaction of special education teachers, their attitudes towards working with children with disabilities, and its effect on trained student teachers’ attitudes.                Methodology and research methods. The authors developed a questionnaire to measure the level of job satisfaction, and a scale to measure the attitudes towards working with children with disabilities in the sample, validity and reliability were verified. The study sample consisted of 71 special education teachers and 71 teacher students who “receive their training with special education teachers”. The degree to which student teachers’ attitudes are affected by teachers’ satisfaction and their attitudes towards working with children with disabilities was determined using multiple linear regression analysis.                Results. The means and standard deviations were extracted to analyse the results of the study, which appeared at an average level of performance on the “attitudes” scale, as the averages ranged from 2.49 to 4.20 and with arithmetic mean as a whole 3.49.                Stepwise regression method adopted in the study introduced predicted variables into the regression equation stepwise, resulting in two statistically significant predictive models at the significance level α ≤ 0.05. The first model, involving teacher job satisfaction and student teacher attitudes towards working with children with disabilities, explained 7% of the total variance. The second model, which also considered teachers’ attitudes, explained a substantially larger portion of the variance, accounting for 64% of the total explained variance of the predictive model for student teachers’ attitudes towards working with children with disabilities.                Scientific novelty. The findings highlight the significant influence of teacher job satisfaction and attitudes on student teachers’ attitudes. The study contributes to understanding of the factors shaping student teachers’ perspectives and underscores the importance of promoting job satisfaction and positive attitudes among special education teachers to foster a supportive learning environment.                Practical significance of this study is that it provides valuable insights for the field of special education and teacher training. By examining the job satisfaction and attitudes of special education teachers towards working with children with disabilities and their impact on student teachers, the study informs educational practices and policies. Promoting job satisfaction and positive attitudes among special education teachers is crucial for creating a supportive environment and enhancing teacher training programmes. This knowledge can guide the development of strategies to improve the preparation of future educators and enhance the quality of special education services for children with disabilities. Overall, the study findings contribute to the field and have practical implications for improving educational experiences and outcomes.